ผลกระทบของอัตราเร็วของแรงกระทำแบบวัฏจักรต่อพฤติกรรมทางกลศาสตร์ของดินเหนียวอ่อนกรุงเทพฯ - พิพัฒน์ ทองฉิม (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The effect of rates of loading and the effecf of testing procedures on the mechanical behavior of soft Bangkok clay were investigated using the cyclic triaxial apparatus. Tests were performed on undisturbed samples collected at a depth of about 6.0- 9.0 m. from a site in Chulalongkorn University. The tested samples were saturated and then consolidated to the prescribed effective confining pressures about 50 kPa and 100 kPa. Shearing under the undrained condition was performed in a stress-controlled manner. Samples were sheared at rates of loading 0.10 and 1.0 Hz. The cyclic loading test was divided into two types: Firstly, A continuous cyclic loading, CC, which the sample was loaded to failure in one step. Secondly, A staged cyclic loading, SC, The number of cycles for each stage of cyclic loading was 15. The excess pore pressure building-up during each step was allowed to dissipate before further application of the larger amplitude cyclic load. The effect of rates of loading on the shear modulus and damping ratio were investigated. An increase of rates of loading from 0.1 to 1.0 Hz had no influence on the shear modulus characteristic. However, the damping ratio slightly decreased. Cyclic loading test results from two testing procedures (the continuous cyclic loading test, CC, and the staged cyclic loading test, SC) were found to give fairly similar strain dependence characteristics of shear modulus and damping ratio.